Odpowiedzi

2009-11-16T21:38:43+01:00
6-(5-x)-4x=
6-5+x-4x=
x-4x=-6+5
-3x=-1/:(-3)
x=0,3(3)
-2 / 0,3(3) = yyy.. :D

8z-2*(5z+6)+4z-4=
8z-10z-12+4z-4=
8z-10z+4z=12+4
2z=16/:2
z=8
trzy czwarte / 8 = 0,75:8=0,09375

mam nadzieje, że chociaz troche pomoglam.
2 1 2
2009-11-16T21:40:00+01:00
Zadanie 1
x=-2
5-(5-x)-4x=
5-(5+2)+8=
5-7+8=
6

zadanie 2
8z-2*(5z+6)+4z-4=
z=¾
(8*¾)-2*(5*¾+6)+(4*¾)-4=
6-2*(¹⁵/₄+²⁴/₄)+3-4=
6-(2*³⁹/₄)+3-4=
6-19,5+3-4=
-14,5
1 2 1
2009-11-16T21:41:44+01:00
6-(5-(-2))-4*-2= 6-7+8= -1+8 = 7

8/1*3/4 -2*(5/1*3/4 +6)+4/1*3/4-4= 4*(15/4 +6)+3 = 4*(15/4+24/4)+3=
4*39/4 +3= 39+3=42

Prosz ;]
1 5 1